How Does the Ageing Population Affect China’s Household Savings Rate? Empirical Study Based on China’s Micro Household Data - Yuan, Haidong; Puah, Chin-Hong; Yau, Josephine Tan-Hwang (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The impact of the ageing population on China’s economy and society is multifaceted, with the impact on household savings rates being particularly important. This study investigates the influence of population ageing on household savings rates, utilizing data obtained from the China Household Finance Survey (CHFS) spanning the period from 2015 to 2019. The study found that ageing has a significant negative effect on household savings rates. This finding suggests that there is a significant life-cycle effect on changes in household savings rates in China, which is not conducive to the formation of a second demographic dividend. From the perspective of mediating variables, population ageing growth reduces household income, thereby further decreasing the household savings rate, with income reduction being the main factor causing the decline in the household savings rate. Additionally, it has been found that the impact of population ageing on the household savings rate exhibits significant heterogeneity between urban and rural areas. The increasing proportion of the elderly population in rural areas has a stronger negative effect on the household savings rate.